Цільові пріоритети регулювання сегментованого ринку праці на регіональному рівні - Красножон, Н. С.; Krasnozhon, N . (КНТУ, 2013)
Стаття присвячена поглибленню розуміння процесів сегментації національного та регіонального ринків праці. Доведено, що інноваційний розвиток сегментованого ринку праці стримується багатьма чинниками-блокаторами. Відповідно, з метою подолання протиріч на сегментованому ринку праці надано практичні рекомендації щодо його регулювання на регіональному рівні за умов інноваційних змін економіки країни. The aim of the article consists in deepening of understanding of processes of market of labour and grant of practical recommendations segmentation in relation to his adjusting at regional level at the terms of innovative changes of economy of country. The article is sanctified to understanding of processes of segmentation national and regional labourmarkets. It is well-proven that innovative segmented market of labour development restrains temper many factors-blockers. With the purpose of overcoming of contradictions at the segmented market of labour practical recommendations are given in relation to his adjusting at regional level on conditions of innovative changes of economy of country. It is possible to draw conclusion on results research, that innovative development of national and Kirovograd labour-markets restrains temper many factors-blockers, that negatively affect quality of labour force, her mobility, adaptive possibilities, that narrows possibilities of the active bringing in of working to participating in innovative processes in the nearest years. Realization of having a special purpose priorities in practice of segmented market of labour of the Kirovograd region development must assist leveling of negative factorsblockers and bringing in of levers that it is assisted to forming of innovative market segment.
Target priorities of the segmented labor market regulation at the regional level
Keywords: регіональний ринок праці; процес сегментації; цільові пріоритети регулювання; механізм; keywords; regional labor market; the process o f segmentation; target priorities regulatory mechanism